ANALISIS NET INTEREST MARGIN (NIM) DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSETS (ROA) SEBELUM DAN SESUDAH KBMI 4 PERIODE 2019-2021 - Arnesia Regista Dewi (2022)
In improving the Indonesian economy, the contribution of the banking sector is very much needed by considering the size of the bank's profits. The amount of profit obtained by the bank can use the ratio of Return on Assets (ROA). The bank's source of profit comes from distributing funds in the form of credit to its customers. The amount of credit provided by the bank is able to generate profits in the form of interest. The net profit value obtained by the bank will be managed first because the profit value must be given to customers who raise funds. To find out the ratio of the difference in the value of profits can use the ratio of Net Interest Margin (NIM). As in increasing the value of profits, banks must incur operational costs for their activities to generate income which can be calculated by the ratio of Operating Costs to Operating Income (BOPO). The purpose of writing this final project is to determine the effect of NIM and BOPO on ROA KBMI 4 for the period 2019-2021. Based on the test results of data analysis that the authors calculated based on the quarterly financial statements, there is an influence between NIM and BOPO with ROA, and there are several supporting phenomena that occur and have an impact on banking profits. Although there are several uncorrelated quarters, most of them are able to state that there is an influence between NIM and BOPO on ROA of KBMI 4 for the 2019-2021 period.